2020
DOI: 10.5935/1415-2762.20200042
|View full text |Cite
|
Sign up to set email alerts
|

Modos de ser de profissionais de enfermagem em terapia intensiva pediátrica

Abstract: Objective: to understand the experiences of Nursing professionals with the families of children hospitalized in a pediatric intensive care unit. Method: this is a qualitative study, using the analysis of the structure of the situated phenomenon as a methodological reference, carried out with 19 Nursing professionals working in the pediatric intensive care unit, of a public hospital in the state of São Paulo. We analyzed the speeches from the interviews according to the guidance of Martins and Bicudo. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The neonatal nursing team's practice still limits parents' participation by requesting that they leave during procedures in which they could be present, such as infusion therapy and several other procedures which their presence does not hinder. This situation is also observed in studies that broaden the discussion on family participation by integrating them into care planning and delivery, including during cardiopulmonary resuscitation and tracheal intubation (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…The neonatal nursing team's practice still limits parents' participation by requesting that they leave during procedures in which they could be present, such as infusion therapy and several other procedures which their presence does not hinder. This situation is also observed in studies that broaden the discussion on family participation by integrating them into care planning and delivery, including during cardiopulmonary resuscitation and tracheal intubation (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…The creation of the group occurred after the analysis of the results of two studies conducted in the unit, which stimulated nurses to promote an intervention aiming to meet the care demands of families of children in PICU (4)(5) . Initially, meetings were held with the multi-professional team of the unit, managers, and teachers to present the proposal and outline the steps for its implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the aspects mentioned above and considering the context of the intensive care unit where the study was developed, it was identified the need to provide support, by the initiative of nurses of the unit, based on the results of two studies conducted there, in which it was evidenced the lack of support and difficulty of the relationship between staff and family (4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation